Ultrasound examination of achilles tendons in patients with familial hypercholesterolemia - V. V. Genkel; M. I. Kolyadich; E. V. Lebedev; A. S. Kuznetsova; R. G. Portnova; I. I. Shaposhnik (Российский кардиологический журнал, 2018)
Aim. To assess the morphometric characteristics of Achilles tendons in patients with familial hypercholesterolemia (FH) and to identify factors associated with an increase in their size.Материал и  методы. Totally, 100 patients included, with severe primary hyperlipidemia, defined as an increase in total cholesterol ≥7,5 mM/L and/or lowdensity lipoprotein cholesterol ≥4,9 mM/L. All patients underwent duplex scanning of carotid arteries. Ultrasound examination of the Achilles tendons was carried out on an expert class ultrasound equipment Samsung Medison EKO 7 (Japan) with a linear sensor, frequency of 7-16 MHz. Thickness of the Achilles tendon (anteriorposterior dimension (APD)) was measured during scanning in the longitudinal section, width (transverse dimension (TD)) — scanning in the cross section. The measurements were made 2 cm proximal to the calcaneus.Results. Among the participants, 32 (32,0%) had definite/probable diagnosis of FH. In patients with definite/probable FH the mean values   of APD were significantly higher in comparison with patients scored 5 or less points (DLCN) — 5,50 (4,70-6,10) mm vs. 5,00 (4,50-5,40), respectively (p=0,04). TD of Achilles tendons among this category of patients was also statistically significantly higher in comparison with the rest of patients — 14,0 (12,9-15,4) mm and 13,2 (12,2-14,2) mm, respectively (p=0,04). In correlation analysis, the relationship between the growth of patients and the APD of the Achilles tendons (r=0,34, p=0,001), the TD of the Achilles tendon (r=0,28, p=0,009), CIMT and TD of the Achilles tendons (r=0,21, p=0,05), amount of carotid plaques and TD of the Achilles tendon (r=0,26, p=0,01), total percentage of stenosis of the carotid arteries and the TD of the Achilles tendons (r=0,27, p=0,01), maximum percentage of stenosis of the carotid arteries and the TD of the Achilles tendons (r=0,28, p=0,007). According to regression analysis, factors associated with an increase in thickness of the Achilles tendons for more than 75 percentiles were male sex, diabetes mellitus, height, myocardial infarction in relatives, total percentage of stenosis of the carotid arteries and high-density lipoproteide cholesterol.Conclusion. In patients with definite/probable FH, mean values of width and thickness of the Achilles tendons were significantly higher in comparison with the rest of the patients. According to regression analysis, the factors associated with the increase in thickness of the Achilles tendons fro more than 75 percentiles were male sex, diabetes mellitus, height, myocardial infarction in relatives, total percentage of stenosis of the carotid arteries and HDL high-density lipoproteide cholesterol.